(untitled) (Research, Society and Development, 2022)
The objective of the study was to evaluate the perception of undergraduate dental students at the Padre Gervásio National Institute for Higher Education regarding the use of Active Teaching Methodology and the portfolio in the teaching-learning process. This is an observational and cross-sectional study. We evaluated 300 randomly selected students, 30 from each term, who answered a questionnaire. Of the participants included in the research, 78% (234) were female and 22% (66) were male; 65% (195) of the participants totally agreed and 30% (90) partially agreed that the Active Teaching Methodology contributed to the development of the capacity to learn and update knowledge autonomously. Regarding the portfolio, 93% (279) of the sixth to tenth period students totally agreed that there was a greater stimulus to improve their performance when they received a sufficient concept in the portfolio and/or praising comments; no student disagreed. Thus, this study indicates that most students are favorable towards the use of the new teaching method and the clinical portfolio. However, the feeling of not being fully prepared for professional practice, without the support of the teacher, is a concern of the students in the last period of the course. This may explain, in part, the results obtained in this group of students.